American radio networks a history - Cox, Jim 1939- (McFarland, 2009)
The net rewards of radioland: with the twist of a wrist -- The proceeds of experimentation: getting ready to play for real -- National Broadcasting Company: the house that Sarnoff built -- Columbia Broadcasting System: the house that Paley built -- Mutual Broadcasting System: the network for all America -- American Broadcasting Company: noble aims, enduring effects -- The regional hookups: local radio gone wide -- Washington watchdogs: safeguarding the airwaves -- Remuneration: the hardest nut to crack -- Czar wars: the empire-builders fight back -- Halcyon days: a showtime sampler -- Sight radio: no renaissance for imagination -- The spinmeisters: rancor among the ranks -- Raconteurial resurgence: the spielers have their say -- Epilogue: when you wish upon a star
Includes bibliographical references and index
Keywords: Geschichte; Radio broadcasting / History / United States; Rundfunk; USA